The Corruption conundrum of the Zuma Presidency (Journal for Studies in Humanities and Social Sciences, 2022)
The Zuma presidency remains the most dramatic since the birth of liberal democracy in South Africa. The decision of the party oligarchy to support Zuma’s ambitions despite. overwhelming reservations about his moral uprightness demonstrates the “low” value placed on personal attributes by South Africa’s political class. This article would through historical and descriptive methods interrogate the forces that brought President Zuma to power, and “why and how” the establishment remained loyal to him through various challenges. In this regard, the article seeks to investigate the conditions which provided the enabling environment for the president of the ruling ANC who doubles as the President of South Africa to be involved in such controversies as the Nkandla probe, state capture, and an alleged rape. The article would analyze the concept of corruption by drawing insight from various perspectives. This would allow us to determine the extent to which some of former President Zuma’s alleged infractions in office can be regarded as corrupt practices. The article advances a thorough cleansing of the political space; this is a process that is expected to permeate the South African society as a whole.
Keywords: Africa National Congress; Jacob Zuma; State Capture; Nkandla; South Africa